Pengaruh Current Ratio, Return on Asset, Net Profit Margin dan Debt to Equity Ratio Terhadap Harga Saham Perusahaan (Studi Empiris Pada Perusahaan Aneka Industri yang terdaftar di Bursa Efek Indonesia Periode 2011-2014) - Septiya Nur Intan Sari; R. Setyo Utomo (Accounting Study Program, Faculty of Economics and Business, 2017)
This study aims to determine the effect of the variables Current Ratio, Return On Assets, Net Profit Margin, Debt To Equity Ratio on Stock Prices of Various Industry Sector Companies listed on the Indonesia Stock Exchange (IDX). The population in this study is the various industrial sectors for the period 2011-2014. The sample selection used purposive sampling. The number of samples used in this study were 13 companies that met the criteria. Methods of data collection using the method of documentation. The analysis technique used is multiple linear regression analysis which previously performed descriptive statistical analysis and classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. As for testing the hypothesis itself using a partial test (t test), simultaneous test (f test) and the coefficient of determination. The results of the partial test of the Net Profit Margin variable have a significant effect on stock prices. While the variables Current Ratio, Return On Assets and Debt To Equity Ratio have no significant effect on stock prices. While the results of simultaneous testing of variables Current Ratio, Return On Assets, Net Profit Margin and Debt To Equity Ratio have an effect on the stock prices of companies in the various industrial sectors.